The Relationship between Alcohol Consumption and Sleep Quality in the Elderly at Deli Serdang Regency - Helena Pryadina Hutauruk; Fazidah Aguslina Siregar; R. Kintoko Rochadi (Britain International for Academic Research (BIAR) Publisher, 2020)
Sleep is one of the basic human needs that is useful for maintaining mental, emotional and health balance when awake. However, physical and physiological changes in the elderly coupled with health status and disease have an impact on the decline in the quality of sleep. The elders usually experience increased sleep latency, inability to initiate sleep, reduced sleep efficiency, sleeplessness, waking up faster, rhythm of sircadian disorders, and increased time for napping. The elders in Deli Serdang Regency chose to consume alcohol to overcome their sleep problems. This descriptive analytic study aims to analyze the relationship between alcohol consumption habits, especially palm wine and sleep quality of elders in Deli Serdang Regency. This study uses a cross sectional design with a quantitative approach. The population in this study were all elders living in Deli Serdang Regency. Sampling was done by purposive sampling technique. The sample size were 153 people and to anticipate the low response rate the sample was added by ten percent to 164 elderly people. The results showed that from simple regression logistic test, it was obtained that the palm wine consumption variable with p score = 0.023 PR = 12.115 (95% CI 1.421 - 103.276). Alcohol consumption factors were factors that are very likely to be changed by controlling excessive drinking (palm wine) alcoholic behavior. It would be better if the alcohol consumption habits (palm wine) were stopped because remembering the long-term effects of alcohol which not only affect the quality of sleep to be bad but also can affect one's health status.